PV-Mini Hydro-Diesel Hybrid System in a Village - Arith, Faiz; Sharafina, Anis; Idris, M. Idzdihar; M. Yunus, Mawarni (IJENS Publishers, 2013)
Nowadays, renewable energy becomes more demanding because of its advantages which are abundant, untapped and environmental friendly. Due to this fact, it is important to have a lot of research to enhance the performance of the renewable energy system. This paper will discuss on design, analysis and performance for optimizing the system using HOMER software in terms of economical and efficiency. The location for this simulation is at Kampung Chuweh, Pulau Banding, Gerik, Perak, which is Orang Asli village. Solar, mini hydro and generator have been used to simulate the system design. All the data and results are provided in this paper.